2016
DOI: 10.1155/2016/7291438
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Action by the Serotonergic System: Behavior and Neurophysiology inDrosophila melanogaster

Abstract: Serotonin modulates various physiological processes and behaviors. This study investigates the role of 5-HT in locomotion and feeding behaviors as well as in modulation of sensory-motor circuits. The 5-HT biosynthesis was dysregulated by feeding Drosophila larvae 5-HT, a 5-HT precursor, or an inhibitor of tryptophan hydroxylase during early stages of development. The effects of feeding fluoxetine, a selective serotonin reuptake inhibitor, during early second instars were also examined. 5-HT receptor subtypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 76 publications
(110 reference statements)
0
73
0
Order By: Relevance
“…5-HT is a major neuromodulator of motor behaviors ( Figure 1A) in many species belonging to different invertebrate phyla. This includes flatworms [58], cnidarians [59], nematodes [60], annelids [61,62], arthropods (insects and crustaceans, [63][64][65]), and mollusks [66][67][68][69]. Part of our knowledge comes from studies investigating the ecological/toxicological consequences of SSRIs used as antidepressants, released in sanitary water, and finally spread in rivers [63,65,[70][71][72].…”
Section: Motor Activity and Locomotionmentioning
confidence: 99%
“…5-HT is a major neuromodulator of motor behaviors ( Figure 1A) in many species belonging to different invertebrate phyla. This includes flatworms [58], cnidarians [59], nematodes [60], annelids [61,62], arthropods (insects and crustaceans, [63][64][65]), and mollusks [66][67][68][69]. Part of our knowledge comes from studies investigating the ecological/toxicological consequences of SSRIs used as antidepressants, released in sanitary water, and finally spread in rivers [63,65,[70][71][72].…”
Section: Motor Activity and Locomotionmentioning
confidence: 99%
“…We focused on receptors for the neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) because of serotonin's role as a neuromodulator [31]. The effects of serotonin depend on receptor-specific binding, and in Drosophila and other insects 5-HT receptors have been associated with variation in locomotion, feeding behavior, learning and memory, and aggression [32,33].…”
Section: Divergence In 5-hydroxytryptamine Receptor 2a (5-ht2a)mentioning
confidence: 99%
“…Serotonin (5-hydroxytryptamine; 5-HT) signalling influences numerous Drosophila behaviours, including sleep (Yuan, Joiner, and Sehgal 2006;Nichols 2007) , courtship (Pooryasin and Fiala 2015) , place learning ) and aversive olfactory conditioning. Flies express five serotonin receptors: 5HT1A, 5HT1B, 5HT2A, 5HT2B and 5HT7 (Johnson, Becnel, and Nichols 2011;Majeed et al 2016;Gasque et al 2013) . Loss-of-function mutants for three of these receptors ( 5HT1B , 5HT2A , and 5HT7 ) have been analyzed by T-maze olfactory conditioning, but no replication studies have been reported.…”
Section: Stm Relies On Serotonin Receptorsmentioning
confidence: 99%